Pemanfaatan Augmented Reality Sebagai Media Pembelajaran Di Perpustakaan SDN 12 Jebus Bangka Barat - Andriyanto, Sidhiq; Pratama, Muhammad Setya; Dewayani, Rossa Julia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Augmented reality technology is often used for student learning media. The use of augmented reality technology is expected to increase the relatively few library visitors at SD Negeri 12 Jebus. Therefore, it is necessary to train library managers to use augmented reality to improve their competence. The tools used are smartphones and markers. training activities consist of material explanation, demonstration, and practice. The result is that participants can use augmented reality applications correctly according to the procedures in the usage module. Learning activities using augmented reality are expected to make students more interested in visiting the library.